Improving service quality, accountability and transparency of local government: The intervening role of information technology governance - Hafiez Sofyani (Taylor & Francis Group, 2020)
This study aims to examine the perception of government employees about the association of the culture of compliance in information technology (IT) on the service quality, accountability, and transparency through effective IT governance (ITG) as an intervening variable. This study was carried out in the local government (city) of Surabaya, Indonesia. The population of this study is all Local Government Organizations (LGOs) in the Surabaya, while the samples are LGOs for public services and administration. Data was gathered through the questionnaires distributed directly to the respondents. The respondents are LGOs employees who are involved with e-government implementation. The number of distributed questionnaires was 200, but there were only 141 returned and analyzed. The partial Least Square-Structural Equation Modeling (PLS-SEM) was utilized to analize the data. The results of this study demonstrate that the culture of compliance in IT associates with service quality, accountability, and transparency indirectly through effective ITG. The result implies that effective ITG is a crucial aspect that must be considered for achieving successful e-government development in Indonesian local governments.